Kapasitas Dinas Kebersihan Dan Pertamanan Pemerintah Kota Medan Dalam Pengelolaan Sampah Di Kota Medan - Aryo Rizki Lumban Toruan; Rudi Krisitian Krisitian P.M (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
Waste management is an activity carried out in an effort to handle and reduce waste which includes of collection, transportation, final disposal and waste processing which aims to improve public health and environmental quality and can make waste as a resource. The research method used in this study is a descriptive method with a qualitative approach. Data collection techniques used to answer research problems are interviews, observation, documentation, and literature study. To check the validity of the data, source triangulation techniques, technique/method triangulation and theoretical triangulation techniques were used. The findings in the research field concluded that the capacity of the Medan City Sanitation and Gardening Service in managing waste in Medan City was not maximized. The capacity of human resources at the Department of Cleanliness and Parks in Medan City needs to be improved because there is no provision of education and training for employees in the field of waste management and the capacity of relations and networks at the Medan City Sanitation and Parks Service currently also needs to be improved because the Medan City Sanitation and Parks Service only maintains working relationships with all sub-districts in Medan City and only pilots collaboration with the private sector in managing waste into compost. .